A Cross-Cultural Analysis of the Infant Behavior Questionnaire Very Short Form: An Item Response Theory Analysis of Infant Temperament in New Zealand. Issue 6 (2nd November 2017) - Peterson, Elizabeth R.; Mohal, Jatender; Waldie, Karen E.; Reese, Elaine; Atatoa Carr, Polly E.; Grant, Cameron C.; Morton, Susan M. B.
ABSTRACT: The Infant Behavior Questionnaire–Revised Very Short Form (IBQ–R VSF; Putnam, Helbig, Gartstein, Rothbart, & Leerkes, 2014 ) is a newly published measure of infant temperament with a 3-factor structure. Recently Peterson et al. (2017 ) suggested that a 5-factor structure (Positive Affectivity/Surgency, Negative Emotionality, Orienting Capacity, Affiliation/Regulation, and Fear) was more parsimonious and showed promising reliability and predictive validity in a large, diverse sample. However, little is known about the 5-factor model's precision across the temperament dimensions range and whether it discriminates equally well across ethnicities. A total of 5, 567 mothers responded to the IBQ–R VSF in relation to their infants ( N = 5, 639) between 23 and 52 weeks old. Using item response theory, we conducted a series of 2 parameter logistic item response models and found that 5 IBQ–R VSF temperament dimensions showed a good distribution of estimates across each latent trait range and these estimates centered close to the population mean. The IBQ–R VSF was also similarly precise across 4 ethnic groups (European, Māori, Pacific peoples, and Asians), suggesting that it can be used as comparable measure for infant temperament in a diversity of ethnic groups.